Attenuated vasodilatation in lambs with endogenous and exogenous activation of cGMP signaling: Role of protein kinase G nitration - Aggarwal, Saurabh (2011)
Pulmonary vasodilation is mediated through the activation of protein kinase G (PKG) via a signaling pathway involving nitric oxide (NO), natriuretic peptides (NP), and cyclic guanosine monophosphate (cGMP). In pulmonary hypertension secondary to congenital heart disease, this pathway is endogenously activated by an early vascular upregulation of NO and increased myocardial B-type NP expression and release. In the treatment of pulmonary hypertension, this pathway is exogenously activated using inhaled NO or other pharmacological agents. Despite this activation of cGMP, vascular dysfunction is present, suggesting that NO-cGMP independent mechanisms are involved and were the focus of this study. Exposure of pulmonary artery endothelial or smooth muscle cells to the NO donor, Spermine NONOate (SpNONOate), increased peroxynitrite (ONOO(−)) generation and PKG-1α nitration, while PKG-1α activity was decreased. These changes were prevented by superoxide dismutase (SOD) or manganese(III)tetrakis(1-methyl-4-pyridyl)porphyrin (MnTMPyP) and mimicked by the ONOO(−) donor, 3-morpholinosydnonimine N-ethylcarbamide (SIN-1). Peripheral lung extracts from 4-week old lambs with increased pulmonary blood flow and pulmonary hypertension (Shunt lambs with endogenous activation of cGMP) or juvenile lambs treated with inhaled NO for 24h (with exogenous activation of cGMP) revealed increased ONOO(−) levels, elevated PKG-1α nitration, and decreased kinase activity without changes in PKG-1α protein levels. However, in Shunt lambs treated with L-arginine or lambs administered polyethylene glycol conjugated-SOD (PEG-SOD) during inhaled NO exposure, ONOO(−) and PKG-1α nitration were diminished and kinase activity was preserved. Together our data reveal that vascular dysfunction can occur, despite elevated levels of cGMP, due to PKG-1α nitration and subsequent attenuation of activity.